(untitled) (Research, Society and Development, 2022)
This article proposes to report the experience about the event “Renal morphology workshop” developed by the Academic League of Nephrology (LANEF) of the Federal University of Alfenas (UNIFAL-MG) intended for students from the first to the last year of medical school. Moreover, it was used an active methodology for consolidation of the study of renal anatomy, through the dissection of swine kidney, once dissection is a pedagogical method that collaborates to the construction of knowledge, and the swine kidney has great similarity to the human organ. Furthermore, the knowledge of renal anatomy is essential to understand the pathophysiology of nephrological diseases. The activity was carried out at the Laboratory of surgical techniques of Medicine School (FAMED) of UNIFAL-MG. Fifty medical students from UNIFAL-MG took part in the activity; twenty five participants in each shift of the event. Dissection kit, gloves, swine kidney, tray, lab coat and the dissection manual with instructions were used. Then, the experience of the event for the league members was extremely important for developing communicative skills and team work, also learning from the act of teaching others. For the participants, the activity allowed them to gain knowledge and review the renal anatomy, also to build an association with the renal physiology and have a solid knowledge about nephrological diseases in the future. Besides, it also allowed some students to have their first contact with surgical instruments.